Antibacterial Effectiveness of Cinnamon Peel Ethanol Extract Toothpaste (Cinnamomum burmanni) In Inhibiting the Growth of Streptococcus Bacteria - Syahdiana Waty; Yetti Lusiani; Aminah br. Saragih (Universitas Islam Negeri Sumatera Utara, Medan, 2023)
Streptococcus is one of the dominant bacteria in the oral cavity. This bacteria is the bacteria that causes dental caries. Toothpaste containing fluoride is important for preventing tooth decay. Using fluoride toothpaste creates a dilemma because it can cause side effects in the form of fluorosis if used in concentrations that are not recommended. However, there is an alternative way, namely by using toothpaste which contains essential oils and plant extracts. The type of research used is the experimental method. The research was conducted at the pharmaceutical laboratory of the Health Polytechnic of the Ministry of Health Medan and the Microbiology laboratory of the University of North Sumatra Hospital, which was carried out from May to July 2023. The samples in this study were dental plaque taken from 30 respondents pre and post intervention application of 12.5% cinnamon bark ethanol extract toothpaste. The data obtained will be analyzed statistically using the non-parametric Wilcoxon test and the parametric Pair T-Test. The results showed that toothpaste with cinnamon bark ethanol extract with a concentration of 12.5% had significant antibacterial activity in inhibiting the growth of Streptococcus bacteria with a p value <0.05. This toothpaste is able to significantly reduce the number of bacterial colonies found in dental plaque in all bacterial groups. It is hoped that these results will provide information to the public that the ethanol extract of cinnamon bark can be used as an active ingredient in toothpaste.Keywords: Antibacterial, Cinnamon bark, Streptococcus, Toothpaste